The Anarchical Society at 40 : contemporary challenges and prospects - Suganami, Hidemi, Ed (Oxford University Press, 2017)
Hedley Bull's 'The Anarchical Society' was published in 1977. Forty years on, it is considered one of the classic texts in International Relations. It does not, however, address many world political issues that now concern us deeply, such as terrorism, global financial crises, climate change, the impact of the internet revolution, deep-rooted racial inequalities, and violence against women. Moreover, while the development of International Relations as an academic subject has consolidated the status of the 'English School' as one of the principal approaches to the study of world politics, and 'The Anarchical Society' as its key text, significant limitations in Bull's approach have also been identified. This volume examines how far 'The Anarchical Society' continues to illuminate world politics and how well Bull's method and argument stand up today. The volume argues that although many of Bull's substantive judgements require updating, his approach remains valuable, not only for thinking about enduring problems of violence and security, but also, as a starting point, for thinking about many issues that Bull himself neglected. However, the contributors also develop important criticisms of Bull's approach and identify ways in which it could be strengthened. A key insight is that although 'The Anarchical Society' is famous for explicating the concept of 'international society', there is more to it than that.